Influence of Nb content on the corrosion resistance and saturation magnetic density of FeCuNbSiB alloys - Mariano, N. A.; Souza, CAC; May, J. E.; Kuri, S. E. (Elsevier B.V., 2003)
Nanocrystalline FeCuNbSiB alloys obtained from the partial crystallization of amorphous alloys have attracted technological attention due to their excellent magnetic properties, but the relationship between corrosion resistance and magnetic properties is not well established. The influence of Nb as an alloying element and effect of partial crystallization on the corrosion resistance of Fe73.5Si13.5B10Cu1, Fe73.5Si13.5B7Nb3Cu1 and Fe73.5Si13.5B5Nb5Cu1 amorphous alloys were studied and the effect of corrosion on magnetization saturation flux density, B-s, was investigated. The addition of niobium on amorphous alloys increases the corrosion resistance. The raise of Nb content from 3 to 5% increases the corrosion resistance also. A partial crystallization increases the corrosion resistance of the samples with Nb. However, in the samples without Nb, the partial crystallization diminishes the corrosion resistance. The values of B-s depend on the alloy corrosion resistance.) (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: FINEMET; corrosion; oxidation; saturation flux density